2017
DOI: 10.1145/3012939
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotically Optimal Encodings of Range Data Structures for Selection and Top- k Queries

Abstract: Given an array A[1, n] of elements with a total order, we consider the problem of building a data structure that solves two queries: (a) selection queries receive a range [i, j] and an integer k and return the position of the kth largest element in A[i, j]; (b) top-k queries receive [i, j] and k and return the positions of the k largest elements in A [i, j]. These problems can be solved in optimal time, O(1 + lg k/ lg lg n) and O(k), respectively, using linear-space data structures.We provide the first study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…This improves upon the trivial ⌈mn log (mn)⌉-bit encoding when m = o(lg n) , and also generalizes the mn(m + 3)∕2-bit encoding [10] for answering queries. The trivial encoding of the input array takes O(nm lg n) bits, whereas one can easily show a lower bound of Ω(nm lg (max (m, k))) bits for any encoding of an m × n array that supports -k queries since at least O(nm lg m) bits are necessary for answering queries [3], and at least n lg k bits are necessary for answering -k queries for each row [11]. Thus, there is only a small range of parameters where a strict improvement over the trivial encoding is possible.…”
Section: Our Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This improves upon the trivial ⌈mn log (mn)⌉-bit encoding when m = o(lg n) , and also generalizes the mn(m + 3)∕2-bit encoding [10] for answering queries. The trivial encoding of the input array takes O(nm lg n) bits, whereas one can easily show a lower bound of Ω(nm lg (max (m, k))) bits for any encoding of an m × n array that supports -k queries since at least O(nm lg m) bits are necessary for answering queries [3], and at least n lg k bits are necessary for answering -k queries for each row [11]. Thus, there is only a small range of parameters where a strict improvement over the trivial encoding is possible.…”
Section: Our Resultsmentioning
confidence: 99%
“…For general k, on a 1D array of size n, Grossi et al [11] proposed an O(n lg k)-bit encoding which supports sorted -k queries in O(k) time, and showed that at least n lg k − O(n) bits are necessary for answering 1-sided -k queries; Gawrychowski and Nicholson [9] proposed a (k + 1)nH(1∕(k + 1)) + o(n)-bit 2 encoding for -k queries (although the queries are not supported efficiently), and showed that at least (k + 1)nH(1∕(k + 1))(1 − o(1)) bits are required to encode -k queries. They also proposed a (k + 1.5)nH(1.5∕(k + 1.5)) + o(n lg k)-bit data structure for answering -k queries in O(k 6 lg 2 nf (n)) time, for any strictly increasing function f. For a 2D array A of size m × n , one can answer -k queries using O(nm lg n) bits, by storing the rank of all elements in A.…”
Section: Previous Workmentioning
confidence: 99%
See 2 more Smart Citations
“…For general k, on a 1D array of size n, Grossi et al [10] proposed an O(n lg k)-bit 1 encoding which supports sorted Top-k queries in O(k) time, and showed that at least n lg k − O(n) bits are necessary for answering 1-sided Top-k queries; Gawrychowski and Nicholson [7] proposed a (k + 1)nH(1/(k + 1)) + o(n)bit 2 encoding for Top-k queries (although the queries are not supported efficiently), and showed that at least (k + 1)nH(1/(k + 1))(1 − o(1)) bits are required to encode Top-k queries. They also proposed a (k + 1.5)nH(1.5/(k + 1.5)) + o(n lg k)-bit data structure for answering Top-k queries in O(k 6 lg 2 nf (n)) time, for any strictly increasing function f .…”
Section: Previous Workmentioning
confidence: 99%